Chlorpromazine inhibits the plasmid-mediated oqxAB multidrug efflux pump in Escherichia coli isolates of Egyptian patients with utis - Kholoud Baraka; Rania Abozahra; Fatma Okda; Sarah M. Abdelhamid (BMC Microbiology)
Abstract Over the past ten years, the prevalence of the OqxAB efflux pump, a plasmid-mediated quinolone resistance determinant, has increased among Escherichia coli (E. coli) isolates. The aim of this study was to genotypically and phenotypically investigate quinolone resistance of isolates and transferability of oqxAB genes by conjugation. One hundred E. coli isolates were collected from UTIs samples and identified using biochemical techniques and confirmed by VITEK-2 System. Antibiotic resistance of isolates was determined by disc diffusion method. MIC of levofloxacin was determined using the broth microdilution method. Efflux pump-mediated resistance was assessed using the chlorpromazine-based efflux-pump inhibitor microplate assay. PMQR genes (oqxA, oqxB) were detected by conventional PCR. A conjugation experiment was run to investigate the transferability of the quinolone resistance in having plasmids carrying oqxAB. DNA sequencing was performed for the identification of genes in both donors and tranconjugants. 80% of E. coli isolates were resistant for levofloxacin. Chlorpromazine significantly decreased the levofloxacin MIC values. oqxA and oqxB genes were detected in 44% and 39% of levofloxacin resistant isolates, respectively. The conjugation experiment revealed the transfer of resistance. MICs of levofloxacin in transconjugants carrying oqxAB significantly increased as compared to the parental recipients MICs. In conclusion, plasmid-mediated quinolone resistance linked to oqxAB may be a factor in rapid rise in and spread of bacterial quinolone resistance among Egyptian E. coli isolates. Chlorpromazine could inhibit efflux pump activity leading to decreased quinolones resistance improving their effectiveness in treatment infectious diseases.